A Foldable Neural Electrode for 3D Stimulation of Deep Brain Cavities. (2016) - Kil, Dries; De Vloo, Philippe; Nuttin, Bart; Puers, Robert
Abstract: In this work a new type of foldable neural electrode is presented. The microfabricated electrode is specifically designed for Deep Brain Stimulation of the cavity wall of thalamic lesions resulting from brain infarcts. On implantation, the electrode is introduced through a cannula, after which the flower-like structure unfolds, contacting the cavity walls and allowing stimulation at different anatomical locations. A three-layer microfabrication process based on UV-lithography and Reactive Ion Etching (RIE) is presented. In-Vivo experiments have also been performed in which the implantation procedure and the unfolding of the electrode are tested and visualized.